2011
DOI: 10.1126/scisignal.2001551
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Tumor Growth Through a Nonclassical Pathway that Includes the Transcription Factors ERβ and KLF5

Abstract: Clinical evidence suggests that antiestrogens inhibit the development of androgen-insensitive prostate cancer. Here, we show that the estrogen receptor β (ERβ) mediates inhibition by the antiestrogen ICI 182,780 (ICI) and its enhancement by estrogen. ERβ associated with gene promoters through the tumor-suppressing transcription factor KLF5 (Krüppel-like zinc finger transcription factor 5). ICI treatment increased the recruitment of the transcription coactivator CBP [CREB (adenosine 3',5'-monophosphate response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 64 publications
9
113
1
1
Order By: Relevance
“…The underlying reasons for this necessitate further investigation. One possibility is insufficient dosing of the therapeutic agents in question (Chadha et al 2008 Nakajima et al (2011) primary human tissue culture (Centenera et al 2012) or xenografts of human tumours (Lawrence et al 2013) may be helpful in this regard. Estrogen-related pathways are clearly of great importance in the development and progression of hormonedependent cancers such as prostate cancer, but the role of ERB remains controversial, with numerous contradictions in the published literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying reasons for this necessitate further investigation. One possibility is insufficient dosing of the therapeutic agents in question (Chadha et al 2008 Nakajima et al (2011) primary human tissue culture (Centenera et al 2012) or xenografts of human tumours (Lawrence et al 2013) may be helpful in this regard. Estrogen-related pathways are clearly of great importance in the development and progression of hormonedependent cancers such as prostate cancer, but the role of ERB remains controversial, with numerous contradictions in the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional paradigm regarding the roles of the two ERs in the prostate is that ERB is predominantly protective, being anti-carcinogenic and pro-apoptotic (Chang & Prins 1999, Horvath et al 2001, Zhu et al 2004, McPherson et al 2010, Muthusamy et al 2011, Nakajima et al 2011, Attia & Ederveen 2012, whereas ERA is oncogenic and promotes cell proliferation and survival , Bonkhoff & Berges 2009, Celhay et al 2010, Attia & Ederveen 2012). This view is based on a range of observations including epidemiological and in vivo studies, preclinical drug trials and expression profiles of the two ERs in human prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated possible roles of KLF5 in the progress of breast carcinomas. In prostate carcinomas, however, KLF5 is considered a better prognostic marker (Nakajima et al 2011) and expression of KLF5 was also reported to be suppressed in prostate cancer (Chen et al 2003). These differences among different types of human malignancies may be partly explained by diversity of the expression patterns of KLF5 responsive genes because KLF5 is known to regulate several different genes associated with cell proliferation (reviewed in ).…”
Section: K Takagi Et Al: Klf5 In Breast Carcinomamentioning
confidence: 99%
“…KLF5 is also known to be involved in important biological processes such as cell proliferation and differentiation (Bieker 2001, Black et al 2001, and its expression is induced by growth stimuli, consistent with its potent pro-proliferating roles (Bieker 2001, Sun et al 2001. Recently, KLF5 has been proposed to be involved not only in normal human tissues but also in their malignant tumors (Tong et al 2006, Kwak et al 2007, Nakajima et al 2011, Soon et al 2011. However, its biological functions and/or clinical significance in human carcinomas have remained largely unknown, which is partly due to the fact that results of previous reports varied among different types of carcinomas (reviewed in ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in transcription of the FOXO1 gene involves the recruitment of KLF5-ERb-CBP (CREB-binding protein) complex to the promoter of FOXO1. The increase in transcription can be opposed by E 2 , which promotes proteasome-dependent degradation of KLF5 (Nakajima et al 2011). This is one possible mechanism through which ERb can oppose E 2 -induced proliferation.…”
Section: Studies On Erbmentioning
confidence: 99%